Prenatal Exposure to Maternal Stress and Neurodevelopmental Outcomes in Children: A Longitudinal Study with Epigenetic Analysis in Jakarta, Indonesia - Fatimah Mursyid; Akmal Hasan; Tomiola Owkwulu; Maximillian Wilson; Yi-Fen Huang; Husin Sastranagara (Sriwijaya Journal of Neurology, 2024)
Introduction: Prenatal exposure to maternal stress has been identified as a potential risk factor for adverse neurodevelopmental outcomes in children. This study aimed to investigate the association between prenatal maternal stress and neurodevelopmental outcomes in children in Jakarta, Indonesia, and to explore the potential mediating role of epigenetic modifications. Methods: A longitudinal cohort study was conducted involving 300 pregnant women recruited from antenatal clinics in Jakarta. Maternal stress was assessed during the second trimester of pregnancy using the Perceived Stress Scale (PSS). Neurodevelopmental outcomes in children were evaluated at 12 and 24 months of age using the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III). Epigenetic analysis of cord blood DNA methylation was performed using the Illumina Infinium MethylationEPIC BeadChip. Results: Higher maternal stress scores during pregnancy were significantly associated with lower cognitive, language, and motor scores in children at 12 and 24 months of age. Epigenetic analysis revealed differential methylation patterns in genes related to neurodevelopment in children exposed to high prenatal maternal stress. Mediation analysis indicated that DNA methylation partially mediated the association between prenatal maternal stress and neurodevelopmental outcomes. Conclusion: Prenatal exposure to maternal stress is associated with adverse neurodevelopmental outcomes in children, and epigenetic modifications may play a mediating role in this relationship. These findings highlight the importance of addressing maternal stress during pregnancy to promote optimal child neurodevelopment.